Cultivating Wellness in Banking: How Organizational Justice and Employee Engagement Combat Job Burnout? - Zubair Ahmed Pirzada; Nazar Hussain Phulpoto; Shoukat Ali Mahar (JISR Management and Social Sciences & Economics)
The primary purpose of this study was to explore how organisational justice influences job burnout through the mediation of employee engagement. To achieve this, the study employed a quantitative positivist etic methodology, surveying 356 employees within the commercial banking sector of Sindh Province, Pakistan, and utilising structural equation modelling (SEM) for data analysis. The findings revealed that justice significantly enhances engagement and reduces burnout. Specifically, OJ predicts approximately 70% of the variance in EE (R2 = 0.698) with a strong path coefficient of 0.838 (T-statistic = 25.659, p-value = 0.000). Additionally, it also explained about 47% of the variance in JB (R2 = 0.469), with a moderate path coefficient of 0.302 (T-statistic = 2.065, p-value = 0.019). Furthermore, EE was found to mediate the relationship between OJ and JB, indicating that fair organisational practices indirectly contributes to reducing burnout levels through enhanced engagement. Along with that, EE mediates the relationship between OJ and JB, with an indirect effect path coefficient of 0.353 (T-statistic = 2.669, p-value = 0.004). The implications of these findings suggest that implementing just organisational practices can effectively balance burnout and enhanced engagement, thereby improving overall employee wellbeing and organisational performance. This research contributes to the existing literature by addressing gaps in understanding how organisational justice affects job burnout and employee engagement in the banking sector of Sindh Province. It provides valuable insights into balancing burnout and enhancing engagement through just organisational practices.